Gender and Transport in the Middle East and North Africa Region : Case Studies from the West Bank and Yemen - World Bank (Washington, DC, 2014)
Mobility is a major factor of access to economic resources, education, health, and other key elements influencing women's empowerment. In the Middle East and North Africa's countries, like in many other developing economies, women's mobility is constrained not only by the limited, sometimes unaffordable transport supply but also by social and cultural factors that frame women's access to the outside world and exacerbate the supply problem. The objectives of this study are: 1) understanding better how transport infrastructure and services are meeting women's transport needs, and more specifically, how they are facilitating or constraining women's access to resources, markets, training, information, and employment; and 2) identifying priority areas for governments' actions to improve women's mobility and thereby enhance their access to economic opportunities and contribute to their economic empowerment. Three studies of the interaction between gender and transport have been conducted with these in mind: one in rural Yemen, one in urban Yemen, and one in the West Bank. Analyses of the findings of the studies have led to the following recommendations being put forth: i) encourage the use of intermediary means of transport; ii) create awareness about women's mobility needs; and iii) identify and mitigate constraints delaying development projects in rural Yemen.